2015
DOI: 10.1128/aem.02253-15
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Containing Nicotine Hydroxylase Genes in a Nicotine Degradation Pathway That Is a Variant of the Pyridine and Pyrrolidine Pathways

Abstract: bOchrobactrum sp. strain SJY1 utilizes nicotine as a sole source of carbon, nitrogen, and energy via a variant of the pyridine and pyrrolidine pathways (the VPP pathway). Several strains and genes involved in the VPP pathway have recently been reported; however, the first catalyzing step for enzymatic turnover of nicotine is still unclear. In this study, a nicotine hydroxylase for the initial hydroxylation step of nicotine degradation was identified and characterized. The nicotine hydroxylase (VppA), which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…BLAST analysis showed that NdhAB is almost identical to the most recently reported nicotine hydroxylase from Ochrobactrum sp. strain SJY1 (24), which mediates the first step in the same pathway, too. However, the function of the nicotine hydroxylase from Ochrobactrum sp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…BLAST analysis showed that NdhAB is almost identical to the most recently reported nicotine hydroxylase from Ochrobactrum sp. strain SJY1 (24), which mediates the first step in the same pathway, too. However, the function of the nicotine hydroxylase from Ochrobactrum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Just like heterologous expression of nicotine hydroxylase from Ochrobactrum sp. strain SJY1 in E. coli (24), ndhAB was not functionally expressed (data not shown), likely because the molybdopterin cofactor in NdhAB was not synthesized by E. coli (29), which normally synthesizes the molybdopterin guanosine dinucleotide (29,61). In contrast, NdhAB from strain S33 may bind a molybdopterin cytosine dinucleotide like Ndh from A. nicotinovorans (29) and isoquinoline 1-oxidoreductase from B. diminuta 7 (48).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations